Influence of impaired chaperone or secretion function on SecB production in Escherichia coli. - Müller, J P (1996)
The efficient export of proteins through the cytoplasmic membrane of Escherichia coli requires chaperones to maintain protein precursors in a translocation-competent conformation. In addition to SecB, the major chaperone facilitating export of particular precursors, heat shock-induced chaperones DnaK-DnaJ and GroEL-GroES are also involved in this process. By use of secB'-lacZ gene fusions and immunoprecipitation experiments, SecB production was studied in E. coli strains containing conditional lethal mutations in chaperone or sec genes. While the loss of heat shock chaperones resulted in an increased production of SecB, mutations in sec genes showed only minor effects on SecB synthesis. Neither the plasmid-mediated overexpression of precursors of exoproteins nor the overexpression of secB altered the synthesis of SecB. These results suggest that under conditions where chaperones become depleted, E. coli responds by raising the expression of secB. These data confirm the supposed synergy of different chaperones involved in protein export.